Peirce’s Early Re-readings of his Illustrations: the Case of the 1885 Royce Review - Girel, Mathias (Cognitio: Revista de Filosofia, 2013)
Abstract: Interpretations of Peirce’s development after 1898 often mix three kinds of arguments: one argument about belief, one argument about philosophy and practice, and one argument about the causal role of James’s writings on Peirce’s development. I shall focus here on the last two points: theory and practice and the alleged role of James. James’s role in Peirce’s development is somewhat overestimated and one can doubt Peirce’s worries about the dogmatic use of the scientific method and of philosophy in morals are conditioned by James’s writings only. Peirce’s re-readings and refinements of his Illustrations started no later than the early 1880s, at a time when James was not as central a reference as it became after 1900 for the philosophic stage. To support that claim, I wish to focus here on one particular point: the distrust towards those who try to “mingle” philosophy and practice is by no means a new theme in the 1890s. One of the most telling examples of such a claim is the 1885 review of Royce’s The Religious Aspect of Philosophy, some thirteen years before the quarrel over pragmatism started.